Identification of a Mitochondrial Defect Gene Signature Reveals NUPR1 as a Key Regulator of Liver Cancer Progression - Lee, Young-Kyoung (Hepatology, 2015)
Many cancer cells require more glycolytic adenosine triphosphate production due to a mitochondrial respiratory defect. However, the roles of mitochondrial defects in cancer development and progression remain unclear. To address the role of transcriptomic regulation by mitochondrial defects in liver cancer cells, we performed gene expression profiling for three different cell models of mitochondrial defects: cells with chemical respiratory inhibition (rotenone, thenoyltrifluoroacetone, antimycin A, and oligomycin), cells with mitochondrial DNA depletion (Rho0), and liver cancer cells harboring mitochondrial defects (SNU354 and SNU423). By comparing gene expression in the three models, we identified 10 common mitochondrial defect–related genes that may be responsible for retrograde signaling from cancer cell mitochondria to the intracellular transcriptome. The concomitant expression of the 10 common mitochondrial defect genes is significantly associated with poor prognostic outcomes in liver cancers, suggesting their functional and clinical relevance. Among the common mitochondrial defect genes, we found that nuclear protein 1 (NUPR1) is one of the key transcription regulators. Knockdown of NUPR1 suppressed liver cancer cell invasion, which was mediated in a Ca(2+) signaling–dependent manner. In addition, by performing an NUPR1-centric network analysis and promoter binding assay, granulin was identified as a key downstream effector of NUPR1. We also report association of the NUPR1–granulin pathway with mitochondrial defect–derived glycolytic activation in human liver cancer. CONCLUSION: Mitochondrial respiratory defects and subsequent retrograde signaling, particularly the NUPR1–granulin pathway, play pivotal roles in liver cancer progression.